Impact of the electrical conductivity on the lithium capacity of polymer-derived silicon oxycarbide (SiOC) ceramics. (20th October 2016) - Kaspar, Jan; Graczyk-Zajac, Magdalena; Choudhury, Soumyadip; Riedel, Ralf
Abstract: Within this work, we systematically investigate the influence of the amount of free carbon phase on the electrical conductivity and the lithium storage capability of silicon oxycarbide (SiOC) materials. A series of SiOC ceramics comprised of free carbon content ranging from 8 to 54 wt.% is examined. The ability to reversibly host lithium ions is correlated with the elemental composition and the electrical conductivity. The materials with low carbon content up to ∼20 wt.% reveal conductivities lower than 3 10 −5 S m −1 and initially high capacities of more than 1000 mAh g −1, which fade rapidly with continuous cycling. For the samples with higher amounts of free carbon phase, higher electrical conductivities ranging from 0.07 to 2.2 S m −1 are measured. In comparison to the carbon-poor materials, the carbon-rich samples demonstrate enhanced accessibility of Li-ion storing sites with capacities of more than 500 mAh g −1 . Moreover, a linear dependence between a stable capacity after 60 cycles and free carbon content in the ceramic is found.